Citra alam: the Malay male teenager characters design principle based on physical form and facial features for action genre / Azri Hilmi Rizalman … [et al.] - Rizalman, Azri Hilmi; Md Shamsul Maarif, Danish; Ahid, Muhammad Hafizudin; Mohd Herrow, Mohd Firdaus; Nazrin, Nizar (Universiti Teknologi MARA, Perak, 2024)
A character in an animation is the primary element to tell a story. The character is a medium to help the audience relate and be interested in a story. Particularly, the race of a character allows the audience to relate to the character’s lifestyle. However, nowadays, many character designs do not represent their race. For example, the characters in Malay animations lack resemblance to Malay individuals. Malaysian artists are influenced by the popularity of Japanese animation or anime, leading them to create characters akin to those in anime. The current research explored the basis of the design and human anatomy of the Malays to develop a guideline for creating a Malay character. Considering that male teenage characters, aged between 13 and 17 years old, are a recent animation trend, the study focused on creating Malay male teenage characters. Accordingly, this research explored the human anatomy through the use of golden ratio measurement to determine the proportions of a Malay male teenager. Other than that, an interview with specialists in the design field was conducted to validate the developed guidelines. The results of this research findings and the measurements can be used to create a guideline for making a Malay character along with some other factors in design. This research can be further improved in the future by including data for other races in Malaysia to have comprehensible guidelines for creating multi-race characters.